Online Learning: Tantangan dan Peluang Pasca Pandemi Covid-19 - Sholihah, Khofifatus; Anbiya, Bakti Fatwa; Qonita, Delvia Ulya (PT The Collaboration UVW, 2023)
The Covid-19 pandemic has forced educational institutions around the world to switch to online learning as an alternative to learning. Even though the Covid-19 pandemic has ended, it is possible for some institutions to take advantage of online learning as an alternative to learning. This article uses a qualitative approach with a library study method to dig deeper into the challenges and opportunities of Online Learning after the Covid-19 pandemic. The main challenges of online learning after the Covid-19 pandemic are the limitations of adequate internet and device access, as well as the difficulties of schools and universities in preparing the necessary infrastructure to support effective online learning. There are also several challenges from the psychological aspect. Such as a lack of social and emotional support and an increased risk of social media addiction. However, online learning also opens up great opportunities for more effective and efficient learning development in the future. Technology can be utilized to improve learning quality and provide a more interactive and interesting learning experience.